Max's Chocolate Chicken - Rosemary Wells (United States Penguin Books Ltd, 1989)
It's springtime for the unflappable young rabbit and his overbearing big sister. Max can hardly wait to gobble up the chocolate chicken on his birdbath, and Ruby wants to plan an egg hunt.
Keywords: Read Aloud